The Politics of Pedagogy: Jesuit Education as Political Threat in the Late Sixteenth-Century Venetian Republic - Moy, Charlotte (The sixteenth century journal, 2019)
Strained relations between the University of Padua and the nearby Jesuit college exploded in 1591: university students vandalized the Jesuit campus, shot muskets, and ran around naked. University professor Cesare Cremonini blamed the Jesuits and successfully lobbied the government to restrict the college to Jesuit novices. This article analyzes works by Paolo Sarpi, Cesare Cremonini, Antonio Possevino, and other Jesuit apologists to argue that Venetian ideals advocated for an education that reflected the religious and political necessities of the local government as one of the foundations of a stable society. Influential Venetians distrusted Jesuit instruction because it was a universal program that was not tailored to the needs of the Venetian government; in reality, however, university education did not entirely fulfill the republic's goals either.